Development and Implementation of Hospital By Laws to Improve Service Quality at RSUD Rupit - Rani, Febrina Hertika; Pettanase, Ismail; Syamsul, Syamsul; Ardha, Dea Justicia; Fakhriah, Syahriati (Pascasarjana Universitas Mataram, 2025)
To create a standardised and compliant service, an Internal Regulation or Hospital by Laws is required, which becomes the operational basis for all medical personnel and hospital staff. This dedicaction is expected to strengthen governance, compliance, and service quality at RSUD Rupit in order to fulfil community expectations and standards set by the government optimally and sustainably. Using empirical research by combining qualitative, participatory, and analytical approaches, so that the review and revision of internal regulations of RSUD Rupit can be carried out systematically to produce better and more effective regulations. A review of the internal regulations (Hospital By Laws) at RSUD Rupit identified several aspects that need to be improved to enhance efficiency and quality of services. The proposed improvements include drafting and writing the content of the regulations. After the review, the team will revise and draft the regulations, and refine the draft based on input from the North Musi Rawas District Health Office, PERSI, and stakeholders. The final draft will be submitted to the hospital leadership and Board of Trustees for review and approval. After that, the regulation will be ratified by the regional head, giving legality and legitimacy to the Hospital By Laws